Post-substitution of magnesium at CaI of nano-hydroxyapatite surface for highly efficient and selective removal of radioactive 90Sr from groundwater. (May 2022) - Sihn, Youngho; Yang, Hee-Man; Park, Chan Woo; Yoon, In-Ho; Kim, Ilgook
Abstract: We have modified the ion-exchange affinity of nano-Hydroxyapatite (Ca5 (PO4 )3 OH, HAP) surface for the rapid and selective adsorption of 90 Sr from groundwater. The modification was achieved by the post-substitution of cations (Na +, Mg 2+, Cu 2+, Ba 2+, Fe 3+, and Al 3+ ) for parent Ca 2+ within surface structure of HAP. The diffraction patterns of modified HAP showed a slight shift of the (002) peak between 25° and 27° 2 θ depending the ionic radius of the substituted cation. Magnesium substituted HAP, Mg-HAP, exhibited the highest removal efficiency (>95%) for 10 ppm of Sr 2+, which is attributable to the higher ion-exchange affinity of substituted Mg 2+ than parent Ca 2+ toward Sr 2+ . The results of various analyses revealed that Mg substitution dominantly occurred at the Ca I site of HAP, which enabled the Mg-HAP to adsorb Sr 2+ at both of Ca I and Ca II sites whereas bare HAP could adsorb Sr 2+ mainly at Ca II site. Adsorption isotherms and the kinetics of Mg-HAP for Sr 2+ were evaluated using a bi-Langmuir isotherm and a pseudo-second-order kinetic model, which demonstrated the Mg-HAP exhibited the highest adsorption capacity (64.69 mg/g) and fastest adsorption kinetics (0.161–1.714 g/(mg·min)) than previously modified HAPs. In the presence of competing cations at circumneutral pHs, the enhanced performance of the Mg-HAP led to a greater than 97% reduction of 90 Sr (initial radioactivity = 9500 Bq/L) within 1 h. The distribution coefficient of Mg-HAP was 1.3–6.6 × 10 3  mL/g while that of bare HAP was 1.2–6.6 × 10 2  mL/g. The findings in the present study highlight that the ion-exchange affinity of Ca I and Ca II sites on HAP surface plays a key-role in 90 Sr uptake. The proposed modification method can simply increase the affinity of HAP surface, therefore, this work can further improve the deployment of an in situ remediation technology for 90 Sr contaminated groundwater, i.e., Mg-HAP-based permeable reactive barrier. Graphical abstract: Image 1 Highlights: The simple post-substitution process could replace parent Ca 2+ by various cations on the hydroxyapatite surface. Magnesium substitution might occur at Ca I site within surface structure of hydroxyapatite. Among the modified HAPs, Mg-substituted hydroxyapatite showed the highest capacity and fastest kinetic for Sr 2+ adsorption. Bi-Langmuir adsorption model could successfully describe the Sr 2+ adsorption behavior by Mg-substituted hydroxyapatite. Magnesium-substituted hydroxyapatite could rapidly and selectively remove >97% of 90 Sr under groundwater conditions.